Microdon tigrinus (Diptera, Syrphidae): Populational fluctuations and specificity to the nest of Acromyrmex coronatus (Hymenoptera: Formicidae) - Forti, Luiz Carlos [UNESP]; Camargo, Roberto S.; Verza, Sandra S.; Andrade, Ana Paula P.; Fujihara, Ricardo T.; Lopes, Juliane F. S. (My University, 2007)
This study was performed in the southern and southeastern regions of Brazil, visiting numerous municipalities, over a period of 25 years, excavating nests of 12 species of leaf-cutting ants of the Acromyrmex genus. Larvae and pupae of Microdon tigrinus were found only in nests of the leaf-cutting ant Acromyrmex coronatus, indicating high specificity. Observation showed that larvae and pupae were well accepted in the nests and the adults, immediately after puparia eclosion and prior to wing distension, were not attacked by the workers, suggesting that they produce semiochemicals for a short time period until they arrive outside the Acromyrmex coronatus nest. It was postulated that these larvae feed on the organic detritus of the nest, as shown for Microdon larvae of other species.
Keywords: Hoverfly; Leaf-cutting ants; Myrmecophilous fly; Acromyrmex; Acromyrmex coronatus; Atta; Diptera; Formicidae; Hymenoptera; Microdon (dipteran fly); Syrphidae